2015
DOI: 10.1111/tri.12642
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus and liver transplantation: where do we stand?

Abstract: SummaryThe hepatitis C virus (HCV) infects more than 180 million people globally, with increasing incidence, especially in developing countries. HCV infection frequently progresses to liver cirrhosis leading to liver transplantation or death, and HCV recurrence still constitutes a major challenge for the transplant team. Antiviral therapy is the only available instrument to slow down this process, although its actual impact on liver histology, in responders and nonresponders, is still controversial. We are now… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 140 publications
(185 reference statements)
0
18
0
Order By: Relevance
“…Median (range) post-LT FU was 9 (6-13) months and 11 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) months for DAA-treated patients and controls, respectively.…”
Section: Post-lt Hcc Recurrencementioning
confidence: 99%
See 1 more Smart Citation
“…Median (range) post-LT FU was 9 (6-13) months and 11 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) months for DAA-treated patients and controls, respectively.…”
Section: Post-lt Hcc Recurrencementioning
confidence: 99%
“…(3) The new era of direct-acting antiviral (DAA) agents has already changed the management approach to HCV infection in the transplant setting. (4,5) It is…”
mentioning
confidence: 99%
“…more effective treatment options in HCV genotype 3, drug-drug interactions), new DAAs against HCV permit to cure more than 90% of HCV positive liver transplanted patients. [36][37][38][39] Thus, when transmitted during LT from HCVD+, recurrent hepatitis could be easily cured, contributing to the further expansion of the use of HCVD+.…”
Section: Use Of Hepatitis C Virus Positive Graftsmentioning
confidence: 99%
“…In addition, many antiviral agents targeting non-structural proteins and host factors involved in HCV replication have been applied in a clinical setting2. On the other hand, re-infection of HCV in drug abusers or recipients of transplanted liver grafts remains a serious problem34.…”
mentioning
confidence: 99%
“…The major differences between primary infection and re-infection of a transplanted liver are as follows: 1) HCV quasispecies escaping from the immune response are already present in the serum at liver transplantation; 2) extra-hepatic HCV can serve as a reservoir for infection of the graft; and 3) the recipients must undergo immunosuppression after liver transplantation3. Several reports have demonstrated that quasispecies were dynamically changed immediately after liver transplantation56.…”
mentioning
confidence: 99%